Author Correction: Mining of efficient microbial UDP-glycosyltransferases by motif evolution cross plant kingdom for application in biosynthesis of salidroside. Issue 1 (December 2017) - Fan, Bo; Chen, Tianyi; Zhang, Sen; Wu, Bin; He, Bingfang
A correction to this article has been published and is linked from the HTML version of this paper. The error has not been fixed in the paper.